How merchandising tool is activated torgovogo business. - Низамова, Н. А.; Багдатов, С. А.; Сванбаев, Е. Е. (Journal of Economic Research & Business Administration, 2015)
This article describes and analyzes the current development of the merchandising in the Republic of Kazakhstan. From the author made a proposal for the development of this sector.